THE ROLE OF PROFITABILITY, LEVERAGE, AND COMPANY SIZE IN DETERMINING STOCK PRICES: A CASE STUDY OF THE MINING SECTOR ON THE INDONESIAN STOCK EXCHANGE - Febriyanti, Ni Putu Putri; Widnyana, I Wayan; Tahu, Gregorius Paulus (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2025)
Stock price is the price per share determined by a company based on the supply and demand of shares in the capital market. Financial performance is considered an important factor in determining stock prices. This study aims to determine the effect of profitability, leverage, and company size on stock prices in mining companies listed on the Indonesia Stock Exchange. The population of this study was all mining companies listed on the Indonesia Stock Exchange for the period 2020-2022, totaling 76 companies. The sample in this study consisted of 21 companies selected using the purposive sampling method. The analysis technique used to test the hypothesis was multiple linear regression analysis. The results of the study prove that profitability has a positive and significant effect on stock prices, leverage has a negative and significant effect on stock prices, and company size has a positive and significant effect on stock prices.